Cloning and expression of the nucleocapsid protein of Newcastle disease virus in Pichia pastoris (Guillierm.) Phaff - Syazwan Saidin (Tanjong Malim, 2010)
Cloning and expression of the nucleocapsid protein of Newcastle disease virus in Pichia pastoris (Guillierm.) Phaff by Syazwan Saidin